Digging deeper : activities for enriching and expanding social studies instruction K-12 - Hickey, M. Gail, 1955-; Clabough, Jeremiah (Teaching and learning social studies., 2017)
Experts in social studies education and gifted education share teacher-tested strategies for differentiating social studies in K-12 classrooms. Chapter authors showcase best-practice and research-based lessons and activities that enrich and expand social studies instruction while building K-12 students' critical and creative thinking. Each chapter contains two or more teacher-tested lessons or activities linking social studies content and concepts to the standards and recommendations of the National Association for Gifted Children (NAGC) and National Council for the Social Studies (NCSS).This edited volume is targeted toward K-12 teachers and administrators, gifted education coordinators and consultants, parents of gifted children, social studies methods instructors, and central office administrators. Each chapter contains activities that can be adapted and replicated in teachers' classrooms.Chapters focus on significant social studies topics such as civic education, historical thinking, drama, and teaching with primary sources. Each topic is approached in ways that meet the needs of gifted education students. Through its emphasis on critical thinking, inquiry-based instruction, and higher order thinking skills, activities and lessons in the book challenge K-12 educators to raise the bar for classroom instruction in ways that improve opportunities of learning for all students.